2022
DOI: 10.3390/jcm11195632
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Tinzaparin in Prophylactic, Intermediate and Therapeutic Doses in Non-Critically Ill Patients Hospitalized with COVID-19: The PROTHROMCOVID Randomized Controlled Trial

Abstract: Hospitalized patients with COVID-19 are at increased risk of thrombosis, acute respiratory distress syndrome and death. The optimal dosage of thromboprophylaxis is unknown. The aim was to evaluate the efficacy and safety of tinzaparin in prophylactic, intermediate, and therapeutic doses in non-critical patients admitted for COVID-19 pneumonia. PROTHROMCOVID is a randomized, unblinded, controlled, multicenter trial enrolling non-critical, hospitalized adult patients with COVID-19 pneumonia. Patients were random… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Nineteen studies had some concerns of bias, mainly because all these studies were open-label. Two studies 32 , 39 had some concerns about the selection of the reported results because they did not report major bleeding or mortality. Only six studies 11 , 16 , 19 , 29 , 30 , 40 were assessed as low risk across all domains.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies had some concerns of bias, mainly because all these studies were open-label. Two studies 32 , 39 had some concerns about the selection of the reported results because they did not report major bleeding or mortality. Only six studies 11 , 16 , 19 , 29 , 30 , 40 were assessed as low risk across all domains.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies were included in the analysis, totaling 1931 patients from all the analyzed studies. [21][22][23][24][25][26][27] The detailed characteristics of included studies are presented in Table 1. Of the included studies, one was an RCT, one was a prospective observational trial, and five were retrospective cohorts.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Our results concur with those of a multiplatform trial and the COVID-PACT trial of critically ill patients, and with the meta-analysis of Ena and Valls that showed that TA reduced macrovascular thrombosis. Of note, 4 of 5 RCTs included in the meta-analysis enrolled patients with high D-dimer levels . However, 2 recent RCTs in critically ill patients reported no benefit of HD-PA use to prevent macrovascular thrombosis .…”
Section: Discussionmentioning
confidence: 99%